Whole-somite rotation generates muscle progenitor cell compartments in the developing zebrafish embryo - Hollway, Georgina E; Bryson-Richardson, Robert J; Berger, Silke; Cole, Nicholas J; Hall, Thomas E; Currie, Peter D (Developmental cell, 2007)
Somites are transient, mesodermally derived structures that give rise to a number of different cell types within the vertebrate embryo. To achieve this, somitic cells are partitioned into lineage-restricted domains, whose fates are determined by signals secreted from adjacent tissues. While the molecular nature of many of the inductive signals that trigger formation of different cell fates within the nascent somite has been identified, less is known about the processes that coordinate the formation of the subsomitic compartments from which these cells arise. Utilizing a combination of vital dye-staining and lineage-tracking techniques, we describe a previously uncharacterized, lineage-restricted compartment of the zebrafish somite that generates muscle progenitor cells for the growth of appendicular, hypaxial, and axial muscles during development. We also show that formation of this compartment occurs via whole-somite rotation, a process that requires the action of the Sdf family of secreted cytokines.